The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/lang.12309
|View full text |Cite
|
Sign up to set email alerts
|

Different Starting Points for English Language Learning: A Comparative Study of Danish and Spanish Young Learners

Abstract: This study compared receptive English grammar skills of two groups of 7‐ and 9‐year‐old Danish children at the beginning of second language (L2) instruction in English, and two groups of Spanish/Catalan children of the same age after several years of instruction. The study examined the influence of two language‐related factors (receptive vocabulary skills, cognate linguistic distance) and two context‐related factors (amount of formal instruction, frequency of exposure to English outside school), additionally f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 67 publications
12
61
0
Order By: Relevance
“…Researchers (e.g., Peters et al., ; Webb, ) have therefore advocated extramural activities as a way of enhancing learners’ vocabulary gains because of their potential for incidental learning. As argued in previous studies (Muñoz, Cadierno, & Casas, ; Sundqvist, ; Sundqvist & Wikström, ; Sylvén & Sundqvist, ), extramural English is related to incidental language learning because the activities that learners engage in do not explicitly focus on language learning. In this study, we adopted Hulstijn's () definition of incidental vocabulary learning, which views incidental learning as being the byproduct of reading or listening activities not explicitly focusing on vocabulary learning, such as playing computer games or watching TV.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Researchers (e.g., Peters et al., ; Webb, ) have therefore advocated extramural activities as a way of enhancing learners’ vocabulary gains because of their potential for incidental learning. As argued in previous studies (Muñoz, Cadierno, & Casas, ; Sundqvist, ; Sundqvist & Wikström, ; Sylvén & Sundqvist, ), extramural English is related to incidental language learning because the activities that learners engage in do not explicitly focus on language learning. In this study, we adopted Hulstijn's () definition of incidental vocabulary learning, which views incidental learning as being the byproduct of reading or listening activities not explicitly focusing on vocabulary learning, such as playing computer games or watching TV.…”
Section: Introductionmentioning
confidence: 83%
“…Further, studies testing learners’ vocabulary size found that scores for cognates were higher than for non‐cognates (e.g., Cobb, ; Laufer & McLean, ). In these studies, the cognate facilitation effect was stronger in older learners, probably because the older learners’ larger vocabulary size in their L1 enabled them to recognize more cognates, resulting in higher cross‐linguistic awareness (Hipfner‐Boucher et al., ; Muñoz et al., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our study had a number of limitations. Research has shown that cognate linguistic distance has an impact on learners’ language proficiency (Lindgren & Muñoz, ; Muñoz, Cadierno, & Casas, ). Even though we controlled for cognates in the vocabulary test, the smaller cognate linguistic distance between Dutch and English than between Dutch and French might still have played a role.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Like these ML learners, immersion learners typically begin young, and have many hours a week of communicative L2 exposure from native speakers (or highly proficient speakers) of the L2. However, like instructed-L2 learners, the exposure that immersion learners receive is largely limited to the classroom in communities where the L2 is a foreign (or minority) language, making them similar to the participants of studies of instructed-L2 classrooms (e.g., Butler & Le, 2018;Muñoz, Cadierno, & Casas, 2018;Sun, Steinkrauss, Tendeiro, & de Bot, 2016). Though immersion contexts are not likely to reach the same quantity of L2 exposure as ML contexts, learners in these programs can amass around 6,000 hr of L2 exposure by their middle-school years (Turnbull, Lapkin, Hart, & Swain, 1998), which far exceeds that of instructed-L2 contexts, for which L2 exposure is limited to only a few hours a week and where total classroom exposure may only be around 800 hr by the end of compulsory education, though this will vary widely by program (Muñoz, 2008).…”
Section: The Immersion-l2 Contextmentioning
confidence: 99%